The Impact of Self-Regulation on Over-Indebtedness Amid the Pandemic - El Fassi, Yasmina (2022)
El Fassi, Y., Pinto, D. C., & Vanneschi, L. (2021). The Impact of Self-Regulation on Over-Indebtedness Amid the Pandemic. In Proceedings of the European Marketing Academy, 50th (pp. 1-2). European Marketing Academy (EMAC). http://proceedings.emac-online.org/pdfs/A2021-94268.pdf -------------------This work was supported by Fundação para a Ciência e a Tecnologia (FCT) [DSAIPA/DS/0113/2019].